ANALYSIS OF PELTON WATER TURBINE DESIGN RESULTS THROUGH VALVE VARIATIONS AND COMPARISON OF NUMBER OF BLADES - Andi Priyanto, Oktavianus; Tugur Redationo , Nereus; Crisanto Putra Mbulu, Bernardus (Universitas Katolik Widya Karya Malang, 2024)
The Pelton turbine is an extension of the impulse turbine, the Pelton turbine operated with high pressure and changes in momentum received by the blades very large. In this research, the researcher wanted to analyze the effect of the number of blades against the momentum force that produces the turbine shaft rotation and generate electrical energy. The research used a mini Pelton type of water turbine, using blades with the number of blades 6, 12, and 18 blades. By using the valve opening ranging from 60o-720o, using an initial load of 150gr, arm length 15cm, then look for the unit conversion of discharge pressure (Pd), turbine head (HT), capacity water (Q), Water Horse Power (WHP), Brake Hourse Power (BHP), and efficiency turbine. The number of blades that are more effective for use in mini-type water turbines Pelton valve opening variations are 18 blades, because of the efficiency and force values greater momentum so that the rotation of the turbine shaft produces a blade 18 with the results of the calculation of the 18 blades obtained a manometer of 215.74 N/m2 turbine head 21.99 m, highest water capacity 0.012 m3/s, highest WHP 26,404 Watts, BHP the highest is 19,765 Watts, and the highest turbine efficiency is 75%.